Determination of trace elements in urine by inductively coupled plasma-tandem mass spectrometry – Biomonitoring of adults in the German capital region. (December 2021) - Schmied, Andy; Murawski, Aline; Kolossa-Gehring, Marike; Kujath, Peter
Abstract: A method was developed and validated for multi-element analyses of human urine samples using inductively coupled plasma-tandem mass spectrometry. The combination of a simple sample preparation and the state-of-the-art technique allows high-throughput and lowest limits of quantification up to 1 ng/L. Thereby coefficients of variation ranges from 0.4% (V) to 3.7% (Be), and 0.9% (Cd) to 4.8% (Ni) for intraday and interday precision, respectively. The method's performance is demonstrated by successful participation in international interlaboratory comparison programs as external quality assurance. Moreover, the method was applied for the analysis of first-morning void urine samples of adults (N = 77) living in the German capital region. 15 metals and metalloids (Astotal, Be, Bi, Cd, Co, Cr, In, Mn, Mo, Ni, Pb, Sn, Tl, V, and Zn) were determined. With exception of indium, all elements were found in urine samples above the limit of quantification, demonstrating the suitability to measure the general population's exposure to these metals and metalloids. The method presented here shall be used for analysis of urine samples collected in the upcoming German Environmental Survey, GerES VI, a cross-sectional, population-representative study. Highlights: Validation of a simple and sensitive ICP-MS/MS method for urine analysis. Performance shown by internal and external quality assurance. Analysis of first-morning void urine samples of non-specifically occupationally exposed adults. Astotal, Cd, Co, Mo, Ni, Pb, Sn, Tl, V, and Zn quantified in 100% of the samples.